The Impact Of Country Of Origin On Consumer Purchasing Preferences For Cars In Tamilnadu - A.SANTHOSHINI; Dr. G. S.SUBASHINI (Journal for ReAttach Therapy and Developmental Diversities, 2023)
The country of origin has a substantial impact on consumer purchase decisions for cars in Tamil Nadu, India. Consumers often associate certain countries with quality, reliability, and brand reputation in the automotive industry. The perception of superior craftsmanship and engineering from countries like Germany or reliability from Japan can positively influence purchase decisions. Cultural and regional preferences also play a role, as consumers may prefer certain aesthetics, design elements, or suitability for local driving conditions. Additionally, the perceived value for money and nationalistic factors can sway consumer choices. However, it is essential to recognize that individual needs, budgets, specifications, after-sales service, and recommendations from peers also influence car-buying decisions. Therefore, understanding the specific preferences and influences of the target audience is crucial when analysing the impact of the country of origin on consumer purchase decisions for cars in Tamil Nadu.